ANALISIS PENGAMBILAN KEPUTUSAN UNTUK PENGADAAN MESIN FOTOCOPY DI PT BCD MENGGUNAKAN PENDEKATAN MODEL MATEMATIKA NET PRESENT VALUE - Riki Ridwan Margana; Alifah Nur Astari (LPPM Universitas Bina Bangsa, 2023)
PT BCD is one of the large distributor companies in Bandung, West Java, which distributes medicines, pharmaceutical equipment and various other consumer goods. PT BCD carries out various activities to support the success of its distribution, one of which is administrative activities in the form of printing sales invoices, tax invoices, printing reports, and archiving reports. Every day, more than 1000 copies need to be printed by a photocopier as reporting and archiving material. By 2024, PT BCD management plans to procure 2 photocopy machines because the old ones often experience problems and cause delays in administrative activities. For this procurement, PT BCD management received offers from several vendors in the form of rental or purchase decisions. Due to this problem, the PT BCD procurement team carried out a decision-making analysis for the procurement of photocopy machines at PT BCD using a mathematical economic model approach using the NPV method. From this analysis, a decision was obtained in the form of selecting Vendor B with a purchasing decision for the photocopy machine procurement activity at PT BCD. This decision was taken because Vendor B with a purchase decision was able to provide the most profitable offer, namely IDR 22,152,300,- when compared to the rental decision which set a price of IDR 48,509,800